CRUSTAL THICKENING AND VARIATIONS IN ARCHITECTURE FROM THE QAIDAM BASIN TO THE QANG TANG (NORTH-CENTRAL TIBETAN PLATEAU) FROM WIDE-ANGLE REFLECTION SEISMOLOGY - Jiang M.; Su H.P.; Wang Y.X.; Galvé A.; Hirn A.; Laigle M.; Lépine J.C.; de Voogd B.; Diaz J. (My University, 2006)
Wide-angle reflection-refraction profiles at crustal scale have been obtained along a 700 km transect of northeastern Tibet from six shotpoints. A combination of sampling by broadside fan-recordings and in-line profiling allows us to image increases in Moho depth towards the centre of the plateau. These occur with different styles across the two block boundaries between North Kun Lun, Bayan Har and Qang Tang, as shown also by the changes resolved in the internal architecture and layer velocities in the crust. Clear S-waves are observed: together with P-waves they bring rare constraints on the composition of crustal units, which reveals an abnormally felsic average composition for the whole crust and its lower half along the whole length of the transect. Across the North Kun Lun-Qaidam block, variations of crustal thickness are detected, with Moho depth between 55 and 65 km, and an inverse correlation with basement topography. In the north of the Bayan Har block, a strong heterogeneity in the middle of the 70 km thick crust is shown. As suggested from synthetic seismograms modelling, it may result from thin layer inclusion marking the northward tectonic superposition of the Bayan Har crust on the North Kun Lun crust. As imaged by a fan profile, the corresponding upper part could have been transported northwards to thicken also the upper crust of the present North Kun Lun block. In the north of Qang Tang, a model is obtained with a 75-km thick crust and a lower half of the crust with average velocities characteristic of felsic composition. From Bayan Har to Qang Tang, variations of deep architecture are documented across the Jinsha suture and Xianshuihe fault from recording in-line and broadside to several shotpoints. Together with the felsic composition of the lower part of the crust, a Moho offset suggests the imbrication of the Bayan Har crust in the Qang Tang lithosphere between a south-dipping Moho above and a north-dipping Moho below. A model of indentation of the Qang Tang by an originally thinner Bayan Har crust and lithosphere, with part of the Qang Tang brought to greater depth would also be consistent also with the Moho topography across the transition from the Qang Tang to Bayan Har, as imaged by fan profile. © 2005 Elsevier B.V. All rights reserved.
Keywords: COMPOSITION; CRUSTAL STRUCTURE; EXPLOSION SEISMOLOGY; SEISMIC ATTENUATION; SEISMIC VELOCITY; TIBET